ANALYSIS OF LAND CERTIFICATE ADMINISTRATIVE GOVERNANCE AT THE LAND OFFICE - Sifa Aprili Yani; Sri Sutjiatmi; Unggul Sugi Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study aims to analyze the administrative governance of land certificates at the Land Office of Tegal Regency in 2024, with a focus on administrative procedures, service programs, the use of technology, and challenges in the issuance of land certificates. The research employs a descriptive qualitative method to gain a deeper understanding of the practices of land administration governance at the regional level. Data were collected through interviews, observations, and documentation studies. Primary data were obtained from interviews with employees of the Land Office who are directly involved in land registration services, while secondary data were derived from official reports and administrative documents. The results indicate that the Land Office of Tegal Regency has implemented several service innovations, such as the Complete Systematic Land Registration Program (PTSL), the Five-Minute Roya Service, and the implementation of electronic land certificates. These innovations are intended to improve service efficiency, strengthen legal certainty, and enhance the security of land data. However, the study also identified several challenges, including limited technological infrastructure, less optimal dissemination of digital services, and public perceptions regarding the quality of services provided. The implementation of electronic land certificates has proven to improve efficiency and data security, yet it still requires stronger human resources and greater technological support. Overall, the study concludes that the governance of land certificate administration in Tegal Regency has moved toward the principles of good governance, although continuous improvements are still necessary.